Pre-exposure prophylaxis for the prevention of HIV infection (PrEP) in women from vulnerable areas of the surrounding area of Buenos Aires (Actualizaciones en Sida e Infectología, 2021)
A series of cases developed in the western region of Buenos Aires, in which there were situations of high risk of HIV infection, are described in order to analyze and explore the potential use of PrEP in women as part of the combined prevention strategy. Although the effectiveness of PrEP is well documented, its implementation is delayed in the region. Women do not seem to be within the considered key populations and therefore far from those strategies. Incorporating the use of PrEP in young women at risk of infection can contribute to the achievement of the objectives of epidemic control and avoid vertical transmission of HIV. The lack of adequate knowledge and the low perception of the risk of infection are described as barriers to a successful implementation.
Keywords: HIV pre-exposure prophylaxis (PrEP); women; surrounding area of Buenos Aires